Tracking mesenchymal stem cell tumor-homing using fluorescent silica nanoparticles. Issue 7 (19th December 2014) - Gao, Yu; Wang, Yaqi; Fu, Afu; Shi, Wei; Yeo, David; Luo, Kathy Qian; Ow, Hooisweng; Xu, Chenjie
Abstract : Core–shell fluorescent silica nanoparticles for in vitro and in vivo tracking of tumor tropism of human mesenchymal stem cells. Abstract : Stem cell tracking can reveal the underlying biological processes of stem-cell-based therapies such as the migration and biodistribution of human mesenchymal stem cells (hMSCs) in cancer therapy. Nanoparticle-based contrast agents offer unprecedented opportunities for achieving this goal due to their unique and tunable imaging capabilities. However, most nanoparticles are still in the process of development due to challenges such as retention time and safety issues, and are inaccessible to most researchers. In this article, we investigate the potential application of core–shell fluorescent silica nanoparticles ( i.e. C dots), which are commercially available and approved by the FDA for clinical trials. Specifically we demonstrate that 500 nm C dots have prolonged cellular retention (up to one month), minimal contrast agent transfer (at least three weeks) between cells in a co-culture Boyden chamber system, and minimal influence on the hMSC properties including viability, proliferation, differentiation, and tropism to tumor cells.